Peran Kementerian Agama Dalam Evaluasi Pengelolaan Pelatihan Mubaligh Untuk Meningkatkan Kualitas Mubaligh Di Kota Parepare - Andi Abdul Salam; Nurhikmah Nurhikmah; Sumarni Sumai; Ramli Ramli; A. Nurkidam (IAIN Padangsidimpuan, 2026)
This research was conducted based on the author's interest in the urgency of training for religious preachers to improve their quality, as well as the issue of inconsistent quality among religious preachers. This research uses a qualitative research type with a phenomenological approach. The data type used in this study is descriptive qualitative data. The research findings indicate that: 1) The role of the Ministry of Religious Affairs in managing mubaligh training is carried out and evaluated by the Islamic Community Guidance Section. In its implementation, the Islamic Community Guidance Section conducts training every year with the aim of aligning the goals and messages of the Ministry of Religious Affairs with the mubaligh. The training for religious preachers also aims to ensure that the quality of preachers is consistent. 2) The Ministry of Religious Affairs does not have specific standards for evaluating the management of mubaligh training, so clear evaluation standards are needed for conducting evaluations. 3) The Ministry of Religious Affairs understands training needs and requires better training concept design. This research is important to understand the role of the Ministry of Religious Affairs in evaluating the management of mubaligh training to improve the quality of da'wah in Parepare City.